TOGOG & SEMAR: DEHUMANIZATION, ANTI-HUMAN, POST-HUMAN - Imam Setyobudi (Universitas Andalas, 2017)
The core of Wayang stories (Mahabharata, Bharatayuda, Ramayana) is the reflection of human that is always continuously in crisis and emergency situations and conditions. Tragic. Wayang stories raise humanity problems so that the existences of human conception experience the perpetuity of dehumanization, existential instability and ambiguous. The killing of the essence of the human existence purpose on earth. It is an issue fundamentally of anti-human.Shadow play perspective does not rest on human understanding or Knight (Pandawa, Kurawa, Rama, Giant), the heaven God (Bathara Guru), and/or Prabu Khresna, incarnation of Wisnhu God. Wayang stories evoke Togog and Semar angle. Liyan. Grassroots. The general public. Amorphous: No Man is not a knight instead of a brahmana is not god instead of giant.Arises a question that is closely related to the presence of Togog and Semar. Why do shadow play stories present the figure of the them, while the authentic story of the Mahabharata and Ramayana India version does not exist at all? Are Togog and Semar truly actualization of post-human aesthetic and post-human anthropology ideas?The substance of this writing ask us to discuss regarding the idea of Togog and Semar in shadow play into the realm of post-human discourse as a result of dehumanization signs in the frame of shadow play stories. The main focus of the discussion focused on the position of Togog and Semar as the figure as linuwih or great beyond human (knight) and god. Study restriction on the context of Purwa Java Gagrak Jogja and Solo wayang; similarly in East Java, Sunda and Bali, there are also those two figures.